A educação não escolar como objeto formativo em cursos de pedagogia no Estado da Paraíba - Silva, Dário Vieira da (2024)
Faced with social, cultural and political transformations in the contemporary scenario, educational practices have increasingly diversified, which has led to a greater insertion of pedagogues in spaces beyond the school. Even so, the Pedagogy course continues to be strongly focused on training teachers for the initial stages of Basic Education, starting in 2006, when the National Curricular Guidelines were approved for the course and, more recently, in 2019, the Curricular Guidelines National Councils for Initial Training of Basic Education Teachers, by the National Education Council. To contribute to the debate on the training of pedagogues for Non-School Education (ENE), this research sought to understand the place of knowledge and training experiences related to this scope in Pedagogy courses in the State of Paraíba, based on the following guiding questions: how does ENE appear in the Pedagogical Projects of Pedagogy Courses (PPC)? What are the perspectives of course coordinators and teachers regarding training for ENE? Thus, the present research aimed to understand the place of ENE in face-to-face Pedagogy courses, offered by Higher Education Institutions (HEIs) based in the state of Paraíba, based on PPC and the conceptions of coordinators and teachers. From a theoretical point of view, the research was guided by references to Pedagogy as a science of education, encompassing a critical view of the initial training of pedagogues centered on teaching, as well as aspects that characterize ENE as a pedagogical practice. From a methodological point of view, it was organized based on the Data-Based Theory (TF) in the constructivist perspective of Charmaz (2009). The empirical field of research consisted of 11 Pedagogy courses, offered by public and private HEIs based in the State of Paraíba. For data collection, documentary mapping of PPC, questionares and virtual interviews were used with course coordinators and teachers. Data analysis occurred through the TFD coding process. The main results of the analysis highlighted the need for a broad debate on the training of pedagogues and the processes of including NSE in the curricula of pedagogy courses at institutions in Paraíba, the importance of professional strengthening in fields where pedagogues work, as well as the establishment of public policies to encourage these processes. The Substantive Theory that emerged from the analysis of the data concludes that, in addition to pointing out the need to expand the Pedagogy curriculum to include Non-School Education, there is a need for the active engagement of course coordinators and teachers in order to guarantee comprehensive training for pedagogues, contributing to the development of practices in their various educational spaces. It is therefore essential to recognize the various professional possibilities, without summarizing their pedagogical work as teaching.